The Impact of Moral Judgment on Consumers' Willingness to Pay More - Vyravene, Revadee; Rabbanee, Fazlul; Ramaseshan, Ram (Griffith University, 2014)
This research is an attempt to answer a recent call from media to examine whether Australian consumers are willing to pay more for their clothes. The media call was based on the premise of a factory collapse in Bangladesh, a key sourcing country of Australian clothing retailers causing a death toll of more than thousand labours. The paper focuses on how the components of a cause-related marketing campaign such as cause-brand fit, cause familiarity and cause importance influence consumers’ moral judgment en-route to their wiliness to pay (WTP) more. Data was collected through a self-administered survey using mall intercept technique. The study revealed that the components of cause-related marketing positively influence consumers’ moral judgement and their WTP. Thus the paper shows evidence that Australian consumers are willing to pay more for their clothes, if the increased price is associated with ensuring well-being of the garment labourers who produce their clothes.